Formation, photoluminescence and in vitro bioimaging of polyethylene glycol-derived carbon dots: The molecular weight effects. (14th March 2022) - Jiang, Yuxiang; Ji, Chunyu; Wu, Jiajia; Han, Qiurui; Cui, Chen; Shi, Wenquan; Peng, Zhili
Abstract: Despite their wide applications, less effort has been devoted for the elucidation of synthesis and photoluminescence mechanism of carbon dots (C-dots), which significantly limits their further developments. In this study, a series of C-dots were prepared from polyethylene glycol (PEG) of different molecular weights (M.W.), and the effects of PEG M.W. on the formation, structural and optical properties of C-dots were carefully investigated. Our study shown that the synthesis of C-dots from PEG went through an "oxidized decomposition – crosslinking – carbonization" process, and as such, the M.W. had a significant influence on the particle sizes, fluorescence intensities, surface chemistry, thermal stability, and bioimaging capabilities of C-dots. These C-dots demonstrated extremely low cytotoxicity and were good agents for cellular bioimaging. Graphical abstract: Image 1 Highlights: A series of C-dots derived from PEGs of different M.W. were synthesized and closely compared. Formation of PEG C-dots mainly went through the "oxidized decomposition – crosslinking – carbonization" process. PEG M.W. heavily influenced C-dots sizes, PL, surface chemistry, thermal stability, and bioimaging capabilities. The PEG C-dots demonstrated extremely low cytotoxicity and were excellent agents for cellular bioimaging.